Food security and nutrition in Bangladesh: Evidence-based strategies for advancement - Ahmed, Akhter; Bakhtiar, M. Mehrab; Mahzab, Moogdho (International Food Policy Research Institute, 2024)
The International Food Policy Research Institute (IFPRI) prepared this report to provide a comprehensive assessment of food security in Bangladesh, with a focus on the core dimensions of availability, access, and utilization.